Insights into the metabolism of the high temperature microbial community of Tramway Ridge, Mount Erebus, Antarctica. Issue 4 (17th February 2016) - Vickers, Chelsea J.; Herbold, Craig W.; Cary, S. Craig; Mcdonald, Ian R.
Abstract: Mount Erebus is the most active volcano on the Antarctic continent, and it has the most geographically and physically isolated geothermal soil on Earth. Preliminary genetic analysis of the microbial community present in the 65°C subsurface soil of Tramway Ridge, on Mount Erebus, revealed a unique high temperature ecosystem, with the dominant members possessing little genetic similarity to known bacteria. This study investigated the metabolism and physiology of this intriguing ecosystem using physical-chemical soil surveying, community-based phenotypic arrays, nutritional enrichment experiments and pyrosequencing. Results have provided new insights into the metabolic requirements and putative roles of specific organisms, as well as the significance of specific carbon and nitrogen sources. In enrichment experiments bicarbonate slowed down an otherwise dramatic shift in community structure. This suggests that bicarbonate maintains the native community in vitro by supplying an essential inorganic compound that is utilized for slow, autotrophic growth. This approach shows potential as a model for future investigations of cultivation resistant thermophilic communities.